2005
DOI: 10.1063/1.1862247
|View full text |Cite
|
Sign up to set email alerts
|

Linear analysis of magnetic and flow shear stabilization of Z-pinch instabilities

Abstract: Articles you may be interested inLinear and nonlinear development of m = 0 instability in a diffuse Bennett Z-pinch equilibrium with sheared axial flow Phys. Linear analysis of sheared flow stabilization of global magnetohydrodynamic instabilities based on the Hall fluid model Phys. Plasmas 9, 913 (2002);A global normal mode stability analysis on the effect of radially sheared azimuthal flow and radially sheared magnetic fields on magnetohydrodynamic ͑MHD͒ instabilities in Z-pinch plasmas is presented. A linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
(7 reference statements)
1
7
2
Order By: Relevance
“…Analytical, experimental and numerical results show that sheared flow in z-pinch plasmas can reduce the growth of MHD instabilities (Arber and Howell, 1995;Bateman, 1978;DeSouzaMachado et al, 2000;Golingo et al, 2005;Shumlak and Hartman, 1995;Sotnikov et al, 2002Sotnikov et al, , 2004Ruden, 2002;Winterberg, 1985Winterberg, , 1999Wanex et al, 2004;Wanex, 2005a). Velocity shear stabilization is primarily a phase mixing process that disrupts the growth of unstable modes (DeSouzaMachado et al, 2000;Wanex et al, 2005b).…”
Section: Collimation Of Astrophysical Jetsmentioning
confidence: 95%
See 2 more Smart Citations
“…Analytical, experimental and numerical results show that sheared flow in z-pinch plasmas can reduce the growth of MHD instabilities (Arber and Howell, 1995;Bateman, 1978;DeSouzaMachado et al, 2000;Golingo et al, 2005;Shumlak and Hartman, 1995;Sotnikov et al, 2002Sotnikov et al, , 2004Ruden, 2002;Winterberg, 1985Winterberg, , 1999Wanex et al, 2004;Wanex, 2005a). Velocity shear stabilization is primarily a phase mixing process that disrupts the growth of unstable modes (DeSouzaMachado et al, 2000;Wanex et al, 2005b).…”
Section: Collimation Of Astrophysical Jetsmentioning
confidence: 95%
“…The use of fixed boundary conditions allows a global stability analysis of internal unstable modes (Arber and Howell, 1995;Appl et al, 2000). It has been shown that sheared azimuthal flow is effective at reducing the growth rate of the kink instability in z-pinch plasmas but has little effect on axisymmetric modes (see Wanex et al, 2005b for a detailed explanation). Sheared axial flow is effective for stabilizing the sausage mode (DeSouzaMachado et al, 2000).…”
Section: Kink Instabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…If such instabilities develop indeed, they should eventually disrupt the jet collimation. On the other hand, axial magnetic fields or radial velocity shears could prevent the disruption (Hsu and Bellan, 2003;Wanex et al, 2005). Jets from young stellar objects are most likely threaded by axial magnetic field (Königl and Pudritz, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…The ideal MHD equation set (1.20) can be used to solve a limited physical problem such as a dense space plasma [10,14,15], to conduct theoretical investigations of instabilities [16][17][18] or to simplify real devices [19,20]. Key in modeling DPP or LPP devices, however, is representing the correct energy exchange and taking into account the main dissipative processes.…”
Section: Nonconvective Termsmentioning
confidence: 99%